2005
DOI: 10.1080/01690960444000250
|View full text |Cite
|
Sign up to set email alerts
|

Why children and adults sometimes (but not always) compute implicatures

Abstract: Noveck (2001) argued that children even as old as 11 do not reliably endorse a scalar interpretation of weak scalar terms (some, might, or) (cf. Smith, 1980; Braine and Rumain, 1981). More recent studies suggest, however, that children's apparent failures may depend on the experimental demands (Papafragou & Musolino, 2003). Although previous studies involved children of different ages as well as different tasks, and are thus not directly comparable, nevertheless a common finding is that children do not seem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(52 citation statements)
references
References 6 publications
3
47
2
Order By: Relevance
“…By encouraging children to actively search alternativeswhich they might otherwise avoid due to the additional effort required -such training might compensate for weak knowledge of scales, allowing children to succeed during the course of the experiment. Consistent with this, training effects are transient, and do not persist after a delay of one week (Guasti et al 2005). By this account, if quantifiers were associated as members of scales (not a processing cost in itself) children would access alternatives without problem, as they do for numerals.…”
Section: General Discussion and Conclusionsupporting
confidence: 49%
See 1 more Smart Citation
“…By encouraging children to actively search alternativeswhich they might otherwise avoid due to the additional effort required -such training might compensate for weak knowledge of scales, allowing children to succeed during the course of the experiment. Consistent with this, training effects are transient, and do not persist after a delay of one week (Guasti et al 2005). By this account, if quantifiers were associated as members of scales (not a processing cost in itself) children would access alternatives without problem, as they do for numerals.…”
Section: General Discussion and Conclusionsupporting
confidence: 49%
“…It is uncontroversial that context affects when and whether children (or adults, for that matter) will compute implicatures (e.g., Guasti, Chierchia, Crain, Foppolo, Gualmini & Meroni 2005;Papafragou & Musolino 2003;Musolino 2006). It is also known that working memory capacity grows over the course of development (e.g., Gathercle & Baddeley 1990).…”
Section: Introductionmentioning
confidence: 99%
“…When presented with underinformative sentences like ''Some giraffes have long necks'', 89% of the children in Noveck's study answered that this statement is true (logical/literal interpretation), while only 41% of the adults responded true. Other developmental studies have confirmed the finding that children do not derive scalar implicatures to the same extent as adults do, even when given more explicit instructions, a training session or acting out tasks that do not require real world knowledge and which are easier for children (Guasti et al 2005;Papafragou and Musolino 2003;Pouscoulous et al 2007). The finding that children's performance improved when manipulating experimental conditions, suggests that it is not merely pragmatic competence as such that is lacking in children, and that limited cognitive resources may be part of the explanation.…”
Section: Scalar Implicaturesmentioning
confidence: 77%
“…This work was also replicated and extended by Guasti et al (2005) with Italian speakers (their Experiment 1). Noveck (2001) implemented an important change to Smith's original design, transforming her questions into declaratives, which expressed a proposition that could be assigned a truth value.…”
Section: Introductionmentioning
confidence: 62%
“…(This is to say nothing of the intense focus on SIs in adult psycholinguistic studies, which we do not review here.) Researchers around the globe have investigated whether children are able to calculate such implicatures (Noveck 2001), and if so, whether their ability to do so depends on the lexical items featured in the experiment (Papafragou & Musolino 2003;Hurewitz et al 2006;Pouscoulous et al 2007), the nature of scalar implicature being targeted (Papafragou & Tantalou 2004;Barner et al 2011;Stiller et al 2015), the amount of contextual and pragmatic support for implicature calculation (Papafragou & Musolino 2003;Guasti et al 2005), the type of judgment children are permitted to provide and the type of task administered (Miller et al 2005;Katsos & Bishop 2011;Foppolo et al 2012;Syrett et al in press), whether children are given evidence for the importance of contrasting scalar alternatives within an experimental session (Vargas-Tokuda, Gutiérrez-Rexach & Grinstead 2008;Foppolo et al 2012;Skordos & Papafragou 2016;Syrett et al in press) and whether implicature calculation is delayed relative to the generation of semantic material (Huang & Snedeker 2009).…”
Section: Introductionmentioning
confidence: 99%